KAJIAN INDEKS PENCEMARAN AIR PADA AREAL PERTAMBANGAN RAKYAT INTAN DAN EMAS DI KECAMATAN CEMPAKA KOTA BANJARBARU - Maulidah Maulidah; Bambang Joko Priatmadi; Suhaili Asmawi; Dini Sofarini (EnviroScienteae, 2015)
This research aimed to determine waters condition based on several water indicators of physical-chemical parameters (TSS, pH, DO, temperature, turbidity, Hg and Fe), mercury’s content of sediment (Hg), and biological parameters of water that is mercury’s content (Hg) of gondang (Pila scutata) the level of water pollution and and analyze in the diamond and gold traditional mining activities at district of Cempaka. The results showed that the water conditions at the station I which is close to the mine site are still fulfill standard of water quality that are temperature, DO and COD according to the results of calculations using the Storet method and included in the category of heavily contaminated. Based of the Pollution Index method categorized low polluted. At the second station which is a mining area, the temperature still fulfill water quality standards, while for the other parameters based on calculations using the Storet method included in the category of heavily polluted. Based on the Pollution Index Method, stations II included in the category of medium polluted. At the third station, which is far from the mine site the parameters of temperature, pH, DO, COD and Fe still water quality standards, but the results of calculations using the Storet method included in the category of heavily polluted. Based on the Pollution Index Method according to Regulation No.82 of 2001, the station III was included in category good condition, while according to the Minister of Health Indonesia No.416/Menkes/Per/IX/90 included in the medium category. So the results of this research for the parameters pH, DO, COD, turbidity, TSS, Fe, Hg water, sediment Hg and Hg gondang not fulfill the quality standards of Government Regulation No.82 of 2001 on Water Quality Management and Pollution Control for the class II and hygienic water requirements in accordance with the requirements of RI Permenkes No.416/Menkes/Per/IX/90.